Cultivo de dos variedades de papa (Solanum tuberosum) var. Libertad y var. Rosita. con abono orgánico y químico en la parroquia Mulaló, cantón Latacunga - Bejarano Albornoz, Adriana Soraya (2011)
The field trial was conducted at the Hacienda San Isidro Parish Mulal, Canton Latacunga, Cotopaxi province, whose location is 00 ° 93'00''south latitude and 78 ° 61'00''west longitude, at an altitude of 2955 meters. The experimental work lasted four months and aimed to assess two varieties of potato (Solanum tuberosum) var. Freedom and var. Rosita with organic manure and chemical Mulal Parish, Canton Latacunga. The design was randomized complete block with factorial 2x3x2 + witnesses a total of twenty-four treatments and three replications was thus 72 experimental units. The results: The highest percentage of emergency was the variety Libertad - Poultry manure-10-30-10 with 87.51%. The average height of the variety Libertad - Cattle manure with 15-15-15 at 120 days was 40.25 cm. Flowering in the range Libertad - Poultry manure was 32.52 days earlier with, in the interaction range - organic fertilizer - chemical fertilizer established that Rosita - -15-15-15 with bovine manure was 38.99 days flowering. The best combination tuber diameter of Freedom - 10-30-10 with 5.51. Number of tubers per plant combination Rosita - 10-30-10 with tubers 9.35 The total weight per plant was given to the number of tubers and average tuber weight, finding Freedom variety - 15-15-15 with the greatest weight to 2.14 kg per plant. The production of potato variety Libertad - Poultry manure-10-30-10 was 34.24 kg / net plot and per hectare was 28.53 t/ha-1 Treatment choice Freedom - Poultry manure - 10-30-10 chemical fertilizer, reported higher revenues to $ 34.24; most optimal utility with $ 5.14 and the best benefit - cost with 0.52